Technical Guidance on Cultivating Red Onion Plants by Applying KCL Fertilizer in North Tanjung Dayang Village, South Indralaya District, Ogan Ilir - Susilawati Susilawati; Benyamin Lakitan; Muhammad Ammar; Firdaus Sulaiman; Erizal Sodikin; M. Umar Harun; Siti Herlinda; Irmawati Irmawati; Fitra Gustiar (Altifani Journal: International Journal of Community Engagement, 2023)
Tanjung Dayang Utara is a village located in the South Indralaya sub-district, Ogan Ilir, South Sumatra. One of the most important inorganic fertilizers frequently used in agriculture is KCl, and considering its role in plant growth, it is crucial to increase the understanding of KCl application for plants. Organic fertilizers, such as chicken manure, are also added to the planting media to provide nutrients in addition to chemical fertilizers. The Bima Brebes variety of shallots are the crops grown in this study, and through this activity, information on shallots and fertilizer was provided, including preparing the planting media and the seedlings, planting, plant maintenance, and harvesting. This activity was carried out from July to September 2023. The activity is aimed at helping the residents of Tanjung Dayang Village comprehend the advantages, nutritional worth, and growth of shallots, as well as the proper techniques of growing shallots, particularly the Bima Brebes variety.